Prognostic value of PD-L1 expression on tumor-infiltrating immune cells and neutrophil-to-lymphocyte ratio in patients with biliary tract cancer - Chen, Shang; Huang, Guizhong; Yao, Zehui; Lin, Xiaojun; Cao, Jianzhong (Frontiers in Immunology, 2026)
BackgroundThe expression of Programmed Death-Ligand 1 (PD-L1) on tumor-infiltrating immune cells (TIICs), plays a crucial role in tumor progression and immune evasion, impacting both the natural immune response and immune-targeted therapeutic strategies. The neutrophil-to-lymphocyte ratio (NLR) has also gained attention as a potential predictive biomarker for immunotherapy efficacy, as it may correlate with treatment outcomes.ObjectiveTo examine the expression of PD-L1 on TIICs and assess the influence of PD-L1 and NLR on immunotherapy outcomes following biliary tract cancers (BTC) recurrence.MethodsFrom January 1, 2017, to January 1, 2020, this study enrolled 239 patients from the Department of Pancreaticobiliary Surgery at Sun Yat-sen University Cancer Center. Immunohistochemical analysis of PD-L1 on TIICs was conducted on pathological tissue sections from these patients. Clinical data, including overall survival (OS), disease-free survival (DFS), and pathological findings, were collected during follow-up. Statistical analyses were performed to assess outcomes related to the study objectives. Furthermore, data from The Cancer Genome Atlas (TCGA) were utilized to examine PD-L1 expression profiles and related information.ResultsTumor stage did not differ significantly (P = 0.173), while metastasis stage approached significance (P = 0.093), with a higher proportion of M0 cases in the PD-L1 low group. Univariate analysis revealed vascular tumor thrombus, tumor differentiation, node stage, and preoperative CA199 levels as factors associated with DFS. Notably, vascular tumor thrombus (HR = 1.791, P = 0.002), moderate tumor differentiation (HR = 0.537, P = 0.002), and elevated preoperative CA199 levels (>35, HR = 1.624, P = 0.009) emerged as significant risk factors. Elevated NLR demonstrated a significant association with reduced DFS (HR = 1.54, p = 0.017 one week prior; HR = 1.70, p = 0.007 one month after) and diminished OS (HR = 2.30, p < 0.001 one week prior; HR = 1.94, p = 0.005 one month after). Exploratory analysis in a limited immunotherapy subgroup (n=35) suggested patients exhibiting high PD-L1 levels on TIICs may be associated with worse OS following immunotherapy after recurrence (HR = 3.03, p = 0.036). High NLR, both one month before recurrence (HR = 2.23, p = 0.015) and one month after recurrence (HR = 2.10, p = 0.027), correlated with decreased OS.ConclusionPD-L1 expression on TIICs and dynamic NLR may be indicative of prognosis in BTC and could provide insights into immune status and response to immunotherapy after recurrence. These findings highlight the potential value of integrating local immune contexture with systemic inflammatory markers, but further validation in larger and prospective cohorts is warranted.